Workplace Values:: Cross-Cultural Insights from the Service Industries - Sledge, Sally; Miles, Angela (Journal of Comparative International Management, 2012)
With the globalization of businesses in recent years, managers must attract and retain the right employees. Part of the fit between a worker and employer is in the area of values. Employees bring personal values to the job and they also are asked to display the workplace values of the organization. Managers must be sure that all workers share the values of the organization. Few studies examine workplace values cross-culturally and qualitatively. Using existing theory, we find that service workers in three countries display workplace values that reflect cultural norms. Managerial implications and directions for future research are given.